The Role of Digitalization and Environmental, Social, Governance in Enhancing Value Relevance of Accounting Information - Handajani, Clarissa Dominique Effendi; Feliana, Yie Ke; Eriandani, Rizky (Jurnal Kajian Akuntansi, 2023)
The acceleration of the Industrial Revolution by the Covid-19 pandemic has enhanced the urgency of digitalization. In addition, the issue of ESG (Environmental, Social, and Government) and the achievement of the triple bottom line have become a major concern for businesses. In contrast, previous research indicates a decline in the value relevance of EPS (Earnings per Share) and BVPS (Book Value per Share) and an enhance in value relevance of non-financial information. This study investigates the effect of digitalization and ESG on the value relevance of accounting information, focusing on EPS and BVPS. This study employs four models with 249 samples from the IDX from 2017 to 2021. Using multiple linear regression, it is determined that, despite the positive significant effect of digitalization and ESG score, the presence of such non-financial information does not enhance the value relevance of accounting information. Moreover, the combination of ESG and digitalization still unable to enhance the value relevance of accounting data. Due to the inefficiency and lack of reporting standard of digitalization and ESG implementation. Therefore, the company should effectively implement and report these data.